Multicenter Phase II Study with Weekly Bendamustine and Paclitaxel as First- or Later-Line Therapy in Patients with Metastatic Breast Cancer: RiTa II Trial - Loibl, Sibylle (S. Karger GmbH, 2011)
The combination of bendamustine (B) and paclitaxel (P) as anthracycline-free treatment option in patients with advanced breast cancer has been evaluated in the previous RiTa I trial. The regimen of weekly B 70 mg/m(2) and P 90 mg/m(2) with a pause every 4th week was established as an effective regimen with low toxicity. The aim of the present RiTa II study was to investigate the potential of BP as anthracycline-free combination therapy. The primary objective was to determine the progression-free survival (PFS); secondary endpoints were safety, tolerability, overall response rate (ORR) and overall survival (OS). 26 patients were available, 15 received BP as first-line, 11 as beyond first-line treatment. 27% patients had triple-negative breast cancer (TNBC). Median PFS and OS were 7.3 months (95% confidence interval (CI): 5.5–10.9) and 14.9 months (95% CI: 9.9–22.9), respectively. The 1-year PFS rate was 20.3% and the 1-year OS rate 71.2%. The ORR was 42.3%, including 4 complete and 7 partial remissions. TNBC patients reached an ORR of 71.4%. Anthracycline-pretreated patients showed an ORR of 43.8%, confirming bendamustine's lack of cross-resistance to anthracycline agents. BP represents a favorable option with moderate toxicity in pretreated metastatic breast cancer and offers a possibility for application in anthracycline-pretreated and TNBC patients.